The effect of spironolactone on diastolic function in haemodialysis patients - Hauser, T. (Int J Cardiovasc Imaging, 2021)
Heart failure with preserved ejection fraction (HFpEF) is highly prevalent in patients on maintenance haemodialysis (HD) and lacks effective treatment. We investigated the effect of spironolactone on cardiac structure and function with a specific focus on diastolic function parameters. The MiREnDa trial examined the effect of 50 mg spironolactone once daily versus placebo on left ventricular mass index (LVMi) among 97 HD patients during 40 weeks of treatment. In this echocardiographic substudy, diastolic function was assessed using predefined structural and functional parameters including E/e’. Changes in the frequency of HFpEF were analysed using the comprehensive ‘HFA-PEFF score’. Complete echocardiographic assessment was available in 65 individuals (59.5 ± 13.0 years, 21.5% female) with preserved left ventricular ejection fraction (LVEF > 50%). At baseline, mean E/e’ was 15.2 ± 7.8 and 37 (56.9%) patients fulfilled the criteria of HFpEF according to the HFA-PEFF score. There was no significant difference in mean change of E/e’ between the spironolactone group and the placebo group (+ 0.93 ± 5.39 vs. + 1.52 ± 5.94, p = 0.68) or in mean change of left atrial volume index (LAVi) (1.9 ± 12.3 ml/m(2) vs. 1.7 ± 14.1 ml/m(2), p = 0.89). Furthermore, spironolactone had no significant effect on mean change in LVMi (+ 0.8 ± 14.2 g/m(2) vs. + 2.7 ± 15.9 g/m(2); p = 0.72) or NT-proBNP (p = 0.96). Treatment with spironolactone did not alter HFA-PEFF score class compared with placebo (p = 0.63). Treatment with 50 mg of spironolactone for 40 weeks had no significant effect on diastolic function parameters in HD patients. The trial has been registered at clinicaltrials.gov (NCT01691053; first posted Sep. 24, 2012).